Covid-19 Pandemic: Financial Impact and Intention to Stay in Current Business of Sabah Tamu Operators - Yaakob, Abdul Rahman; Lily, Jaratin; Idris, Sidah; Jamrin, Zuraidah (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In Sabah, Malaysia, a traditional market known as Tamu (means meeting) acts as a hub for local business activity, especially indigenous people. This paper presents an exploratory study whose goal is to investigate the Covid-19 pandemic financial impact and intention to stay in the current business of Tamu operators. Using purposive and snowballing sampling, survey data were collected from 125 Tamu business operators in Sabah. Among the respondents, 61.6 percent indicated Tamu business as their primary income and main entrepreneurial platform. The Covid-19 pandemic Movement Control Order (MCO) enforcement resulted in the Tamu entrepreneurs experiencing 34.2 percent decrease in weekly sales revenue and a 25.7 percent reduction in weekly gross profit. Furthermore, the overall mean score for the Tamu operators' intention to remain in the Tamu business is high at 4.37 based on 5-point likert scale. Thus, the Sabah Tamu operators are more likely to sustain their Tamu business despite the adverse financial impact of the Covid-19 MCO enforcement. This study outcome may guide the relevant government agencies to mitigate the financial impact by formulating and implementing appropriate policies and support programs specifically targeted for the Tamu business operators, who are mostly informal entrepreneurs.